Usury vulnerability: measuring and modelling the phenomenon in Italy - Stefanizzi, Sonia; Lysova, Tatiana (Quality & quantity, 2024)
Usury has been predominantly studied as an economic or legal phenomenon and only recently has gotten into the spotlight of sociological research. This article aims to contribute to the current literature by operationalising usury vulnerability and analysing household factors impacting it, using the European Union Statistics on Income and Living Conditions (EU-SILC) data for Italy. To construct usury vulnerability, we examined variables measuring a household’s financial and material well-being. As to factors impacting the phenomenon, we included those reflecting a socio-demographic position of a household (household composition and territorial position within the country, age, sex, education, and employment status of the top earner). The estimation results indicate that all micro-level factors matter in terms of usury vulnerability. Therefore, by identifying the most vulnerable social groups, the model might help develop relevant policy interventions to fight the spread of usury, especially in times of economic decline.